Characterization of Clinical Manifestations in the Co-occurring Phenotype of Attention Deficit/Hyperactivity Disorder and Autism Spectrum Disorder - Carta, Alessandra; Fucà, Elisa; Guerrera, Silvia; Napoli, Eleonora; Valeri, Giovanni; Vicari, Stefano (Frontiers in Psychology, 2020)
Comorbidity between attention deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) is a frequently reported condition. However, the clinical overlaps between the two disorders are not well characterized. The Child Behavior Checklist (CBCL) is a well-documented measure of emotional and behavioral problems in children and adolescents. The aim of the present study was to evaluate whether CBCL scales were able to detect psychopathological comorbidities as well as emotional and behavioral profiles across three groups of children with ASD, ADHD, and with the co-occurrence of both disorders. The results show that around 30% of participants with ASD exhibited internalizing problems, which was in line with previous findings. Co-occurrence condition showed a clinical intermediate phenotype: relative to ADHD and ASD, youths with co-occurrence of ADHD and ASD phenotype showed respectively lower (p < 0.000) and higher externalizing problems (p < 0.000). No differences emerged in internalizing problems (p > 0.05) across groups. CBCL is a useful measure to study the psychopathological conditions as well as emotional and behavioral profiles associated with ASD, ADHD, and the co-occurrence of ADHD and ASD. The identification of psychopathological and behavioral profiles associated with ASD and ADHD is crucial to perform specific and individualized treatments. Our preliminary findings suggested the existence of an intermediate and independent phenotype between ADHD and ASD that seems to be defined by the externalizing problems. Internalizing problems do not significantly differ between the combined phenotype and the two groups.